Towards sustainable collaborative networks for smart cities co-governance. (February 2021) - Ben Yahia, Nesrine; Eljaoued, Wissem; Bellamine Ben Saoud, Narjès; Colomo-Palacios, Ricardo
Highlights: Governing a smart city is about promoting sustainable collaborative networks. Study of co-governance performance fosters smart cities policy making perspectives. Robustness, flexibility and efficiency affect co-governance performance. Abstract: This paper addresses the concept of collaborative governance in the context of smart cities, with a focus on supporting and recommending performing organizational structures for sustainable collaborative networks (SCN). It highlights that governing a smart city is about promoting an effective environment of collaboration in the government and implying adaptive policy-making to construct new, internal and external human collaborations. Considering the smart governance as a collaborative network of government agencies and external stakeholders including citizens and a socio-technical system, we conduct in this paper an ethnographic mixed method by combining a qualitative method that studies actors' collaboration and engagement in co-governance with a quantitative method that is based on graph theory to provide numerical analyses of organizational structures. While the qualitative method aims to discover organizational "smart factors" that affect the performance of SCN structures or configurations, the quantitative method aims to find "smart indicators" and metrics to evaluate these organizational factors. The result of this mixed method is an analytical recommender framework of the relevant SCN organizational structures in terms of robustness, flexibility and efficiency.